Hydatid liver cyst open in gallbladder - Ríos Bruno, Guaymirán; Gateño Yaffe, Nisso J (Cirugía del Uruguay, 1972)
The authors relate a.n open liver hydatid cyst observation in the gall bladder. This type of complication is rare and a correct intraoperatory diagnosis is important from the point of view of therapy.